Expression of Androgen Receptor in Human Placentas from Normal and Preeclamptic Pregnancies - Te-Yao Hsu; Kuo-Chung Lan; Chih-Chang Tsai; Chi-Yu Ou; Bi-Hua Cheng; Men-Yin Tsai; Hong-Yo Kang; Yu-Hsia Tung; Yi-Hush Wong; Ko-En Huang (Elsevier, 2009)
Objective: To elucidate the expression of androgen receptor (AR) in human placenta from normal and preeclamptic (PE) pregnancies. Materials and Methods: This study was performed at the Division of Obstetrics and Gynecology, Kaohsiung Chang Gung Memorial Hospital, Academic Medical Center. Forty normal pregnant women at 37.0 ± 0.89 weeks' gestation and 40 women with preeclampsia at 35.9 ± 1.33 weeks' gestation were included in this study. Serum testosterone was measured before delivery. Immunochemical methodology was employed in formalin- fixed, paraffin-embedded sections from the placentas of all subjects. AR expression was evaluated in placentas collected from 15 normal pregnant women and 12 PE women. Results: Women with preeclampsia had an elevated serum testosterone level (0.52 ± 0.13 vs. 0.34 ± 0.11 ng/mL; p < 0.01). The expression of AR in both placentas was confirmed using immunohistochemistry and was primarily present in the nucleus and cytoplasm of syncytiotrophoblasts and stromal cells. There was a significant increase in AR mRNA expression in PE placentas compared with normal placentas. Conclusion: These data suggest that the increased AR expression may alter AR-mediated function on syncytiotrophoblasts and stromal cells in PE placentas, and be a possible mechanism for its association with preeclampsia.